Influence of the insecticide pyriproxyfen on the flight muscle differentiation of Apis mellifera (Hymenoptera, Apidae) - Fernandez, Fernanda Correa [UNESP]; Da Cruz-Landim, Carminda [UNESP]; Malaspina, Osmar (Wiley-Blackwell, 2012)
The Brazilian africanized Apis mellifera is currently considered as one of the most important pollinators threatened by the use of insecticides due to its frequent exposition to their toxic action while foraging in the crops it pollinated. Among the insecticides, the most used in the control of insect pragues has as active agent the pyriproxyfen, analogous to the juvenile hormone (JH). Unfortunately the insecticides used in agriculture affect not only the target insects but also beneficial nontarget ones as bees compromising therefore, the growth rate of their colonies at the boundaries of crop fields. Workers that forage for provisions in contaminated areas can introduce contaminated pollen or/and nectar inside the beehives. As analogous to JH the insecticide pyriproxyfen acts in the bee's larval growth and differentiation during pupation or metamorphosis timing. The flighty muscle is not present in the larvae wingless organisms, but differentiates during pupation/metamorphosis. This work aimed to investigate the effect of pyriproxyfen insecticide on differentiation of such musculature in workers of Brazilian africanized honey bees fed with artificial diet containing the pesticide. The results show that the bees fed with contaminated diet, independent of the insecticide concentration used, show a delay in flight muscle differentiation when compared to the control. Microsc. Res. Tech. 75:844848, 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: juvenile hormone; histology; bees; laboratory brood rearing